A COMPREHENSIVE REVIEW OF EXPERIMENTAL ANIMAL MODEL INDUCTION BASED ON SYNDROME DIFFERENTIATION IN TRADITIONAL CHINESE MEDICINE (Vietnam Journal of Community Medicine, 2026)
Objective: To classify and synthesize methods for establishing experimental animal models based on syndrome differentiation in traditional medicine.Methodology: This study was conducted as a scoping review in accordance with the PRISMA-ScR guidelines. Literature was searched in PubMed, CNKI, and Google Scholar from January 2004 to June 2025. Extracted data included animal species/strains, induction interventions, syndrome validation criteria, objective outcome measures.Results: Of the 40 records initially identified, 18 articles were assessed in full text, and 16 experimental studies met the eligibility criteria. Integrated disease–syndrome models were the most prevalent (n = 7, 43.7%), followed by conversion models (n = 5, 31.3%) and syndrome-only models (n = 4, 25%).Conclusion: Experimental animal models based on TCM syndromes have increasingly evolved toward integrated disease–syndrome models, supporting research on integrated traditional and modern medicine. No eligible Vietnam-based publications were identified within the specified search strategy.
Keywords: Animal model, Traditional Chinese Medicine syndrome, disease-syndrome model, Zheng-hou (syndrome pattern), modeling methods.